Implementasi Sistem Rujukan Pasien Digital Terpadu Menggunakan Metode Deskriptif Kualitatif Untuk Optimalisasi Layanan Kesehatan - Shidiq, Farihan; Romli, Moh. Ali (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The patient referral process at Bidan Mawar Clinic is still carried out manually using paper forms and telephone communication, which often causes delays and recording errors. This condition hampers coordination between midwives and community health centers (Puskesmas) and potentially reduces the quality of healthcare services. To address these issues, this study develops a web- and mobile-based patient referral system aimed at improving efficiency, accuracy, and the speed of the referral process. The research approach employs a descriptive qualitative method, including stages of needs analysis, system design using Unified Modeling Language (UML), and system implementation using Flutter for the mobile application, PHP and Express.js for the backend, and MySQL as the database. The implementation results show that the system can perform login, registration, referral data submission, and real-time status monitoring functions with a 100% success rate under normal testing scenarios. The developed system accelerates the referral process by up to twice as fast compared to the manual method, reduces administrative errors, and enhances coordination between midwives and Puskesmas. Therefore, this system contributes to improving the efficiency and quality of healthcare services at the primary healthcare level.